Uji Validitas Konstruk dengan CFA dan Pelaporannya - Jahja Umar; Yunita Faela Nisa (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2020)
Confirmatory Factor Analysis (CFA) is the most reliable method of construct validity analysis in the fields of psychology, education and social sciences. From the author's observations on research articles as well as bachelor and graduate theses, and dissertations using CFA, it was found that there are a lot of misunderstandings and incompleteness in reporting CFA analysis. This paper is intended as an effort to improve this situation and provide recommendations in reporting data analysis using CFA. At the very least, this article is to show the important things that must be considered in understanding and using CFA and test theory in general.